Group-based fast data packet attribute authentication in the reconfigurable networks. Issue 4 (1st October 2016) - Jia, Hongyong; Chen, Yue; Lan, Julong; Yue, Wei; Wang, Zhiwei
Abstract: The reconfigurable networks in the Chinese national basic research project- Flexible Architecture of Reconfigurable Infrastructure can adjust its own structure to provide better services for applications according to their transactional attributes and is compatible with today's networks. Data packet authentication is necessary to guarantee that precious resources in the reconfigurable networks couldn't be abused. In this paper, we propose a novel fast data packet authentication scheme for the reconfigurable networks based on the attribute based signature and RSA accumulator. In our scheme, packets are organized and authenticated in groups. Every group only needs one signature to guarantee the authenticity of the first packet, and other packets in the group can be verified using the membership witness of RSA accumulator embedded in the packet. The proposed scheme can greatly reduce the generation and verification time of the packet authentication information. Simulation results demonstrate the practicality and efficiency of the proposed scheme.